KORELASI PANJANG EKOR DAN PANJANG TUBUH TERHADAP JENIS KELAMIN ULAR SANCA BATIK (Python reticulatus - Slamet Raharjo; Dionisius M. .; Guntari Titik Mulayni; Soedarmanto Indarjulianto; Ida Tjahajati (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2008)
The unique of Python reticulatus has been studied, however the correlation of the length and body weighthaven't studied yet. This objective ofthe research was to study the correlation of the tail and the body length ofPython reticulatus. Ten Python reticulatus, 2 weeks of old, were used in this research. The snakes wereplaced in individually cage at room temperature, consumed I to 2 mice and white mouse weekly and water adlibitum. The tail and body length of the snakes were measured at the beginning and the end of this research.The datas were analyzed using correlation regretion method. The result of this experiment showed that therewas a significan correlationbetweenthe lengthand body weight (R=O,85).The result of this research showedthat there is a significan correlation with R=O,98 in male snake, and R=O,71 in female snake. It's means thatthere is correlation between tail and body length on Python reticulates sexing.Key words: Python reticulatus, tail and body lengt, sexing